Investigation on the energy consumption of department store in Thailand - Det Damrongsak (2019)
© 2019 The Authors. Published by Elsevier Ltd. This article investigated on the energy consumption of department stores in Thailand. Multiple linear regression has been developed to find the relationship between electrical energy consumption and various variables. It was found that electrical energy consumption obtained from the forecast model were very close to electrical energy consumption from the actual data. The difference of electrical energy consumption from between the forecast model and actual data is approximately 2%. Thus the developed regression model could be served as a baseline sitting used to forecast energy consumption in department stores and determine which variables have major impact on changes in the electrical energy consumption in department stores.